Prognostic factors varying with age in patients with aneurysmal subarachnoid hemorrhage. (June 2020) - Kanamaru, Hideki; Kawakita, Fumihiro; Asada, Reona; Miura, Yoichi; Shiba, Masato; Toma, Naoki; Suzuki, Hidenori; ,
Highlights: Prognostic factors limited to elderly SAH patients have been little reported. Prognostic factors differ between elderly and younger SAH patients. The association of most of known prognostic factors increases with aging. Many known factors independently influenced outcomes in younger SAH patients. Aging made most of known prognostic factors less important in elderly SAH patients. Abstract: With the advent of an aging society, more elderly patients with aneurysmal subarachnoid hemorrhage (aSAH) have been treated. We investigated if prognostic factors differ with age in aSAH patients. In a prospectively maintained aSAH database at multiple institutions from 2013 to 2016, 238 patients who underwent clipping or coiling for a ruptured aneurysm within 48 h of onset were divided into elderly (≥75 years; 57 patients) and non-elderly groups, or categorized into 4-age groups (<54, 55–64, 65–74, and ≥75 years). Prognostic factors and clinical characteristics were retrospectively analyzed. The elderly group had a higher incidence of pre-morbidities, co-morbidities, poor admission World Federation of Neurological Surgeons (WFNS) grades, modified Fisher grade 4, and resultantly 90-day poor outcomes (modified Rankin scale [mRS] 3–6). Multivariate logistic regression analyses revealed that independent determinants for poor outcomes were hypertension and modified Fisher grade 4 in the elderly group, and admission WFNS grades IV–V, systemic complications, non-procedural cerebral infarction and shunt-dependent chronic hydrocephalus in the non-elderly group. The 4-age group analyses showed that higher age group was more frequently associated with the prognostic factors. As higher age itself causes poor outcomes and more association of prognostic factors, prognostic factors in elderly patients may be rather limited.